MULTIAXIAL INVESTIGATION OF PVC FOAMS AND ANALYSIS OF THE DEFORMATION MECHANISM BY 3D-DIC - Francesca Concas; Stefan Diebels; Anne Jung (Acta Polytechnica CTU Proceedings)
Closed-cell polyvinylchloride (PVC) foams are widely used as core for sandwich composites for applications, in which multiaxial loads are involved. In the present work a wide range of uniaxial (tension, compression and torsion) and multiaxial experiments (both simultaneous tension-torsion and compression-torsion) were conducted on a high performance PVC foam. Failure data for each experiment were collected and depicted in the invariants plane. The whole cylindrical surface of the specimen was monitored by means of an 8-camera-system, strain fields were obtained by 3D-DIC. Hence, the occurrence and the evolution of deformation bands were inspected. The usage of an 8-camera system was essential for the observation of the deformation mechanism, especially for pure compression, pure torsion and combined axial load-torsion, in which the arising of deformation bands is affected by the occurrence of buckling and the orthotropy of the foam.